1985
DOI: 10.1007/bf00581789
|View full text |Cite
|
Sign up to set email alerts
|

Contraluminal phosphate transport in the proximal tubule of the rat kidney

Abstract: In order to study the characteristics of contraluminal phosphate transport the stopped flow microperfusion technique [13] has been applied. By measuring the time-dependent decrease of interstitial 33Pi concentration at different starting concentrations a simple diffusion kinetics with a permeability coefficient of 7.5 +/- 1.0 X 10(-8) cm2 s-1 was found. Such a kinetic was so far only observed with 2-deoxy-D-glucose. This substance, however, is transported in addition by facilitated diffusion as was seen by par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…As illustrated in figure 1, there is evi dence that Pj leaves the cell via two different Pj transport systems. Based on experiments with isolated basolateral membranes and intact tubular preparations there is evidence for a sodium-independent DIDS-sensitive anion exchange mechanisms possibly involving bi carbonate ions [14,15]: this transport mecha nisms does not seem to transport sulfate. In addition, a Na-dependent transport pathway for P, has been demonstrated with basolateral membranes isolated from dog kidney [16] and a cultured renal epithelial cell line (OK cells) [17] , In contrast to the apical Na/P, cotran sport, Na-dependent transport of P, through the basolateral membrane is characterized by a low K," value for Pt (millimolar range) and a stoichiometry of 1:1 [6, 17], Heterogeneity o f P, Transport Systems.…”
Section: Basolateral Exitmentioning
confidence: 99%
“…As illustrated in figure 1, there is evi dence that Pj leaves the cell via two different Pj transport systems. Based on experiments with isolated basolateral membranes and intact tubular preparations there is evidence for a sodium-independent DIDS-sensitive anion exchange mechanisms possibly involving bi carbonate ions [14,15]: this transport mecha nisms does not seem to transport sulfate. In addition, a Na-dependent transport pathway for P, has been demonstrated with basolateral membranes isolated from dog kidney [16] and a cultured renal epithelial cell line (OK cells) [17] , In contrast to the apical Na/P, cotran sport, Na-dependent transport of P, through the basolateral membrane is characterized by a low K," value for Pt (millimolar range) and a stoichiometry of 1:1 [6, 17], Heterogeneity o f P, Transport Systems.…”
Section: Basolateral Exitmentioning
confidence: 99%
“…This transport system has wide substrate specificity with a necessity of a negative or partial negative charge on a hydrophobic backbone, but the system also interacts with non-ionisable hydrophobic compounds. The saturable transport of cortisol at physiological concentration was also shown by these studies, and this process was inhibited by probenecid (Ullrich et al 1991). Recently it was demonstrated that adrenocorticotroph hormone (ACTH)-stimulated cortisol release from primary bovine adrenocortical cells was inhibited by probenecid and trans-stimulated by PAH (Steffgen et al 1996 andRohrbach et al 1997).…”
Section: The Multispecific Organic Anion Transport System (Oat)mentioning
confidence: 75%
“…However, in vitro studies demonstrated retention of steroids against a concentration gradient at the plasma membrane (Whitehouse et al 1971, Inaba et al 1974, whereas the interaction of steroids with carrier proteins in cell membranes has been shown in several studies (Rao et al 1997, Raven et al 1982, Thompson et al 1995, Ullrich et al 1991, Chen et al 1996. Moreover, the recently cloned organic anion and organic cation transporter families proved to be able to transport different steroids (Burckhardt et al 2000).…”
Section: Cellsmentioning
confidence: 99%